Penerapan Metode Diskusi Pada Pembelajaran Muatan Matematika Sebagai Upaya Meningkatkan Hasil Belajar Peserta Didik di Kelas V SDN 98/X Rantau Indah Semester Ganjil Tahun Ajaran 2021/2022 - Eka Wijayanti (Journal on Education, 2022)
This study aims to describe and obtain information on increasing the activity and learning outcomes of mathematics through the discussion method. This research is a classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation and reflection. The subjects of this study were students of class V SDN 98/X Rantau Indah, totaling 18 people. This research was conducted in the odd semester of the 2021/2022 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results showed that the discussion method could improve the learning outcomes of the fifth grade students of SDN 98/X Rantau Indah's mathematics content.